Micro-porosity and minero-petrographic features influences on decay: Experimental data from four dimension stones. (10th June 2018) - Scrivano, Simona; Gaggero, Laura; Gisbert Aguilar, Josep
Highlights: Associated MIP and hygroscopic sorption are effective in the characterisation of micro-porosity. Joint MIP and hygroscopic sorption allowed detecting the presence of hygroscopic clay minerals. Mineralogical and petrographic features allowed interpreting the results of the two techniques, when contrasting. On the whole the suggested methodology allowed deciphering the simulated weathering processes. Abstract: Sedimentary stones have been used since long as dimension stones, constituting the primary building material of several monumental structures all over the world. The understanding of their behaviour when exposed to weathering factors is crucial for preservation, replacement and restoration intervention. Although not directly involved with decay mechanisms, micro-pores ( i.e. open pores with radius <0.1 µm) and their interconnection to the wider ones are important for air and water flow inside rocks. In fact, micro-pores are not directly the site of ice or salt crystallization, nor of oil and gas entrapment, but are the main pathway for fluids during both adsorption and evaporation processes. The study of narrow pores is therefore crucial to predict e.g. stone durability and physical properties. This study presents the study on four different sedimentary lithotypes vastly employed as dimension or ornamental stones in Italy, both sound and artificially weathered. In particular, coupled MIP and hygroscopic sorption based micro-porosimetry were used to uncover liability to relative humidity variation, in association with a thorough mineralogical characterization. The MIP intrusion pattern attained pore shapes and typology description for the different rock types; but only the hygroscopic sorption helped deciphering the on-going processes. Moreover, the coupling of petrography and petro-physical analyses ( i.e. MIP and hygroscopic sorption based micro-porosimetry) pointed out that phyllosilicates have a role in decay processes of rocks due to swelling and/or suturing of the adjacent voids.